Green Synthesis of Silver Nanoparticle using Anthurium andraeanum Leaves Extract for High School Practicum Module - Ratri, Monica Cahyaning; Verina, Amadea Agnes (Orbital: Jurnal Pendidikan Kimia, 2024)
Nanotechnology is a new subject in the Merdeka Curriculum that presents challenges in the chemistry learning process. Teachers need help delivering nanotechnology material due to a lack of understanding of the material and teaching materials. Therefore, a practicum module for synthesizing silver nanoparticles based on green chemistry was developed. The objectives of this study were (1) to know the quality of the practicum module in terms of feasibility and (2) to know the teacher's response to the developed module. The results of this study indicate that (1) Anthurium andraeanum leaves have the potential as a bioreductor for the synthesis of silver nanoparticles based on the color change of the silver nanoparticles solution and based on the absorption of UV-Vis spectrophotometer light at a wavelength of 438 nm which shows the characteristics of silver nanoparticles. (2) The developed practicum module has met the criteria of being highly valid, with a percentage of 93% in terms of media and 88% in terms of material. (3) The teacher's response to the developed product is very good, with a percentage of 98%. The developed practicum module is suitable for use in learning nanotechnology.